Antibacterial Effect of Semendo Coffee Beans (Coffea Canephora) Extract Against Streptococcus Sanguinis In Vitro Growth - Sulistiawati; Bambang Nuryadi; Akhyar Dyni Zakyah; Atikah Suci Vidyasari (Denta Journal Kedokteran Gigi, 2021)
Background: Streptococcus sanguinis is one of the most dominant bacteria in early colonization of plaque formation. Robusta coffee beans (Coffea canephora) was reported to have antibacterial properties because it contained compounds such as alkaloids, flavonoids, saponins, tannins, and steroids. Purpose: This study aimed to determine the antibacterial effect of Semendo coffee beans extract to inhibit the bacterial growth of S. sanguinis. Material and method: This study was an in vitro experimental laboratory. This study used Robusta coffee beans origins from South Sumatera called Semendo coffee beans. The treatment group used Semendo coffee beans extract with concentrations of 2.5%, 5%, 10%, 20%, and 40%. The positive control used 0,2% chlorhexidine gluconate and the negative control used sterile distilled water. The antibacterial potency test was used dilution method to MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration) test, and disk diffusion method to inhibitory zone test. Result: The result showed that the MIC of Semendo coffee beans against S. sanguinis couldn't be determined because it was blocked by the color of the extract while MBC was 5%. The average diameter of the inhibition zone formed on 2.5% Semendo coffee beans extract was 12,0±0,4082 mm and bigger along with higher concentration. These results suggested that the extract of Semendo coffee had an antibacterial effect against the growth of S. sanguinis on 2,5%-40%.